Adobe After Effects CS3 - Ferguson, Dwayne; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
Inthis course, Dwayne Ferguson, a professional animator and television art director will show users step by step, how to get the most out of this powerful application. User will learn the interface, cameras and lighting, animation and more
Title from container
Trainign CD
Contains 125 movies with total time 7 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Adobe After Effects; Image processing -- Digital techniques; Cinematography -- Special effects -- Data processing; Digital cinematography